A systematic review of Calendula officinalis extract for wound healing. Issue 5 (20th June 2019) - Givol, Or; Kornhaber, Rachel; Visentin, Denis; Cleary, Michelle; Haik, Josef; Harats, Moti
ABSTRACT: Use of complementary and alternative medicine for wound healing is influencing mainstream medical practice. This systematic review evaluates the role of Calendula officinalis flower extract as monotherapy compared to control for wound healing in vivo. Searches were conducted in PubMed, EMBASE, Cochrane Central Register of Controlled Trials, CINAHL, and Scopus (up to April 2018) with 14 studies meeting the inclusion criteria, comprising 7 animal experiments and 7 clinical trials. Findings from the review on acute wound healing showed faster resolution of the inflammation phase with increased production of granulation tissue in the test groups treated with extract. These findings were consistent in five animal studies and one randomized clinical trial. Chronic wound healing studies were varied. Two clinical control studies on venous ulcers demonstrated decreased ulcer surface area compared to controls. Another randomized clinical trial demonstrated no improvement for the calendula group in diabetic leg ulcer healing. Burn healing similarly showed mixed results. Two animal studies demonstrated a prophylactic effect for the administration of calendula extract prior to burn injury. A randomized clinical trial of patients suffering from partial to full thickness burns demonstrated no benefit for topical application of calendula extract compared to controls. Two randomized clinical trials assessed the potential for extract to prevent acute post radiation dermatitis, with one study showing improvements compared to trolamine, while the other found no improvement compared to aqua gel cream. Animal studies provide moderate evidence for improved recovery from the inflammation phase and increased production of granulation tissue in calendula extract treatment groups. This review identified some evidence for the beneficial effects of C. officinalis extract for wound healing, consistent with its role in traditional medicine. There is a need for larger, well‐designed randomized control trials to assess the effect of calendula on wound healing including complications.